Imaging features of ALK-positive histiocytosis with neurological involvement: a case report and literature review - Wang, Juan; Zheng, Yan; Xiong, Ying (Frontiers in Oncology, 2024)
Background: ALK-positive histiocytosis is an exceptionally rare neoplasm of histiocyte that predominantly involves the nervous system, and can also affect the skin and other parts of the body. Previous relevant literature has provided limited information regarding the imaging manifestations of this disease with neurological involvement. Methods: We reported a case of ALK-positive histiocytosis with multisystem involvement. Together with a comprehensive literature review, the imaging characteristics of this disease in the nervous system were summarized. Results: A 3-year-old girl with abdominal pain and ambulation difficulty checked in to the Department of Pediatric Neurology. The initial diagnosis was "acute cerebellitis with ataxia" based on elevated protein level in the cerebrospinal fluid (CSF). However, despite three months of treatment, the condition deteriorated. MRI showed an oval-shaped, intradural extramedullary nodule at T6-T7 level. The patient was ultimately diagnosed as ALK-positive histiocytosis, accompanied by cauda equina and skin involvement. The literature review showed a total of 23 patients who had involvement of the nervous system and provided imaging descriptions. Together with our case, the imaging features were summarized as follows: iso-dense or slightly hyperdense on computed tomography (CT), isointense or iso-hypointense on T2-weighted imaging (T2WI), moderate homogeneous enhancement with mildly/markedly punctate enhancement or/and smooth ring-enhancement on contrast-enhanced T1-weighted imaging (T1WI), restricted diffusion on diffuse weighted imaging (DWI) and elevated fluorodeoxyglucose (FDG) uptake on positron-emission tomography/ computed tomography (PET/CT). Conclusion: The multimodal imaging findings of ALK-positive histiocytosis exhibit distinct characteristics, familiarity with which will enhance radiologists' expertise and facilitate accurate diagnosis of this disease.